Risk factors of pelvic organ prolapse at Asella Teaching and Referral Hospital: Unmatched case control study - Obsa, Mohammed Suleiman; Worji, Tahir A.; Kedir, Nemo A.; Kute, Negeso G. (Frontiers in Global Women's Health, 2022)
Background Prolapse is one of the sub-types of pelvic floor dysfunction (PFD) which occurs due to abnormal fall of the pelvic organs from their normal anatomic positions. Although the cause of prolapse is multifactorial, it primarily occurs due to pregnancy and vaginal delivery. Hence, the present study aimed to identify risk factors of prolapse among women who undergo gynecological surgery. Materials and methods Facility-based-unmatched case–control design was employed. Cases were all gynecological women who were diagnosed with pelvic organ prolapse (POP) at Asella teaching referral hospital (ATRH) while controls were all charts of gynecological women who were diagnosed with other gynecological problems rather than POP at ATRH. For each case, two controls were selected using a simple random sampling technique. The data were entered into Epidata version 4.3.1 and finally exported to SPSS version 25 for further analysis. Then variables that had an association in the bivariate model (p < 0.25) were entered and analyzed by a multivariable conditional logistic regression model to identify the independent effect of different factors. Statistical significance was declared at p < 0.05. Results A total of 147 cases and 293 controls were included in this study. Women who had a history of chronic cough, previous pelvic floor surgery, constipation, and vaginal tear during delivery, history of pelvic trauma, age of the women, rural resident, and maternal gravidity were strongly associated with prolapse at p-value of < 0.05. Multigravida [adjusted odds ratio (AOR) 2.987 (95% CI 1.237–6.853), p = 0.014], age >50 years [AOR: 2.496 (95% CI 1.372–4.539), p = 0.003], women with a history of pelvic floor surgery [AOR: 0.3.666 (95% CI 1.328–10.124), p = 0.012], women who had diabetes mellitus [AOR: 4.676 (95% CI 0.908–24.075), p = 0.065], and resided in rural areas [AOR = 1.878; (95% CI: 0.984–3.585), I2 = 47.5%, p = 0.056] were the independent predictors were of prolapse. Conclusions In this study, women with diabetes mellitus, previous pelvic floor surgery, rural residents, being multigravida, and age >40 were independent predictors of prolapse. Therefore, delivering health education by focusing on the identified risk factors was strongly recommended.